2020
DOI: 10.1038/s41567-020-01055-5
|View full text |Cite
|
Sign up to set email alerts
|

Directional self-locomotion of active droplets enabled by nematic environment

Abstract: Active matter comprised of self-propelled interacting units holds a major promise for extraction of useful work from its seemingly chaotic out-of-equilibrium dynamics. Streamlining active matter to produce work is especially important at microscale, where the viscous forces prevail over inertia and the useful modes of transport require very specific non-reciprocal type of motion.Here we report that microscopic active droplets representing aqueous dispersions of swimming bacteria Bacillus subtilis show a unidir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 64 publications
8
80
0
Order By: Relevance
“…Each filament organization drives a characteristic largescale vesicle shape transformation that can be selected by varying parameters such as filament length, density, and flexibility. Asymmetric states lead to net vesicle motion, consistent with the recent experiments which find that enclosing self-propelled particles, such as bacteria, in droplets can lead to collective motility [40]. We present simple scaling analyses that reveal how the feedback between vesicle geometry and filament organization drives and stabilizes these emergent behaviors.…”
Section: Introductionsupporting
confidence: 82%
“…Each filament organization drives a characteristic largescale vesicle shape transformation that can be selected by varying parameters such as filament length, density, and flexibility. Asymmetric states lead to net vesicle motion, consistent with the recent experiments which find that enclosing self-propelled particles, such as bacteria, in droplets can lead to collective motility [40]. We present simple scaling analyses that reveal how the feedback between vesicle geometry and filament organization drives and stabilizes these emergent behaviors.…”
Section: Introductionsupporting
confidence: 82%
“…Instead of performing random trajectories in threedimensional geometry, recent experiments have shown that flagellated microorganisms (e.g. E. coli, B. subtilis, and P. mirabilis) move parallel to the nematic director (anisotropy axis) in a biocompatible LC, namely a solution of water and biocompatible compound DSCG (disodium cromoglycate) [10][11][12][13][14][15]. The motion of elongated bacteria parallel to the nematic director can be explained by the minimization of elastic energy of the medium around a rodlike body.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid crystals, used as a medium for active colloids, offer a much higher control level over the microscale dynamics thanks to their longrange orientational order [4,8,9]. In particular, by designing patterns of the nematic director n (n ≡ − n, n2 1) that specifies the preferred direction of molecular orientation [10], one can command the polarity and geometry of propulsion trajectories [11][12][13][14][15][16][17][18], mediate transitions from individual to collective modes of propulsion [17] and control the spatial distribution of microswimmers [14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that a nematic liquid crystal not only directs a microscale motion but could also enable it, as demonstrated by nonlinear electrokinetics [8,11] and by steady directional propulsion of active droplets dispersed in a thermotropic nematic [18]. In the latter case, a spherical water droplet containing randomly swimming bacteria shows directional motility along the overall director [18]. The motility results from rectification of the chaotic flows inside the droplet by the orientationally ordered exterior.…”
Section: Introductionmentioning
confidence: 99%